(re)thinking the new normal after the Covid-19 pandemic: the reality of undergraduate chemistry students at a Higher Education Institution in Bahia/Brazil (Olhar de Professor, 2020)
The emergence of the pandemic caused by COVID-19 brought to reality a face of uncertainty, fears, reflections. Faced with this frightening scenario, society needed to (re) reinvent itself and we started to live the “new normal”. The current concept of normality has changed the social and educational fields, bringing remote education to the reality of Brazilian education. Remote education, unlike Distance Education, can contribute to the increase of social inequalities, since it does not consider basic accessibility issues. In this study, we seek to discuss the diverse and vulnerable context of undergraduate students in the Chemistry Degree course at a Higher Education Institution in Bahia, to attend an online extension course. To this end, we send questionnaires to students, in order to investigate conditions for remote access to Digital Technologies. The data collected revealed that part of the students have difficulties in accessing distance to digital resources.
Keywords: Remote Education. Technological Accessibility. COVID-19.